Genital ulcers caused by sexually transmitted agents, - Mauro Cunha Ramos; Maria Rita Castilhos Nicola; Natália Tenório Cavalcante Bezerra; José Carlos Gomes Sardinha; Julia Sampaio de Souza Morais; Antônio Pedro Schettini (Anais Brasileiros de Dermatologia, 2022)
Abstract Genital ulcers (GUs) represent a diagnostic challenge and can be secondary to neoplastic and inflammatory processes of different causes. Among those of infectious etiology, there are sexually transmitted infections (STIs), a very frequent reason for seeking the health service. The most common agents are herpes simplex virus and Treponema pallidum and, more rarely, Haemophilus ducreyi, Klebsiella granulomatis and Chlamydia trachomatis. A careful dermatological examination offers important diagnostic elements; however, atypical manifestations are very common. Distinctive characteristics of ulcers to look out for include their margin, edge, bottom, and base. Regional lymph node chain alterations should be evaluated regarding their number, size, mobility, consistency, inflammation, and pain on palpation. Diagnostic tests have variable sensitivity and specificity, and molecular tests are currently considered the reference exams. The rapid immunochromatographic tests represented a significant advance, as they can be performed with blood obtained from the digital pulp, offer results in up to 30 minutes, and do not require a laboratory structure. The treatment of persons affected by GU/STIs must be immediate, as it aims to prevent complications, as well as reduce transmission. It is not always considered that people with GUs/STIs have varying degrees of depression, anxiety, and self-reproach, with an impact on relationships. Establishing a bond and trusting the professional is essential for adherence to treatment and preventive measures that must be discussed individually.